Does Impact of Entrepreneurial Literacy and Digital Literacy on a Businessmen Who Influences the Strategy to Maintain SME in The Pandemic Era? - Sulistyowati, Raya (Technium Social Sciences Journal, 2021)
The current pandemic condition, SME players must be to adapt and expand their business strategy from conventional ones to digital ones, such as Facebookads, InstagramBusiness, Shopee, Lazada, OLX, Bukalapak, etc. The purpose of this research is to conduct a comprehensive study of the impact of entrepreneurial literacy and digital literacy on business actors who influence strategies to maintain SMEs in the Pandemic Era. This research was conducted us descriptive qualitative methods by means of observation, documentation and interviews. Viewed from the point of view of the place of research, this research is included in the type of field research field research. Entrepreneurial literacy and digital literacy can generate entrepreneurial, independent and creative spirit. Impact entrepreneurial literacy has been considered as an important factor for growing and developing entrepreneurial passion, spirit and behavior among SMEs. Entrepreneurial literacy can shape mindset, attitude, and behavior of being a true entrepreneur, thus leading them to choose entrepreneurship as a career choice. Digital literacy is very effective in being used as a survival strategy in the era of the Covid pandemic. The sophistication of digitalization functions as a means of carrying out promotional activities, making it easy to exchange information with anyone through existing facilities.